A rapid method for large sample number extraction of proteins from mammalian cells - Packeer Mohamed, Vasila; Hashim, Yumi Zuhanis Has-Yun; Amid, Azura; Mohd Salleh, Hamzah; Yusof, Faridah; Mel, Maizirwan (Tissue Engineering and Regenerative Medicine Society of Malaysia, 2012)
Finding the best method of cell lysis and extraction of protein is the key step in detection and identification of proteins in all applications of proteomics. The methods currently used for protein extraction from mammalian cells are usually laborious, expensive or insufficiently reliable. Recently, researchers working with mammalian cells conduct protein extraction widely and frequently. This frequent dealing with a large number of samples becomes tedious work. Even though there are many commercial lysis buffers on the market, they are usually expensive. Therefore, in this study, protein extraction lysis buffer was designed to provide highly efficient total protein extraction from cultured mammalian cells. The simple and unique composition of this lysis buffer containing sodium dodecyl sulphate (SDS) dissolves cell membranes and extracts total cellular protein in only 45 minutes. The novel extraction method and lysis buffer composition was formulated using classical optimization or one factor at a time (OFAT) study. In this method, cell pellet from mammalian cells (CHO-K1) were subjected to different lysis buffer treatment procedure and then incubated at room temperature. The SDS-PAGE was performed to confirm the proteins extracted. The method was extended to bacteria (Escherichia coli, BL21-AI), yeast (Pichia pastoris) and repeated for mammalian (CHOK1) for confirmation. It yields complete extraction for bacteria and mammalian cells. As such, this lysis buffer when used for preparing protein extracts from bacteria and mammalian cells offers rapid, reliable and cheap protocol which is applicable to routine laboratory analysis especially for protein estimation and SDS-PAGE.